Escenarios de idoneidad agrícola para cultivos peruanos Musa paradisiaca L. y Coffea arabica L. con modelamiento EcoCrop-FAO-SIG, 2021-2040 y 2041-2060 - Aldana Yarleque, Cristhian Nicolás (2024)
The analysis of agricultural-environmental suitability contributes to appropriate land-use planning, land distribution and sustainable agriculture. Using future scenarios of agricultural suitability 2021-2040 and 2041-2060 for Peruvian crops Musa paradisiaca L. and Coffea arabica L., it was evaluated whether the agro-climatic conditions between 1970-2000, marginal and optimal ranges of temperature, precipitation, growing period from days to germination Gmin and Gmax, are adequate in a spatio-temporal dynamic. The EcoCrop-FAO model and GIS information extracted from WorldClim and processed with QGIS, generated spatial distribution maps from agro-climatic-environmental data; obtaining three output indices, crop suitability with respect to temperature (Tsuit), crop suitability with respect to precipitation (Rsuit) and the Suitability Index for Future Crop Suitability (SUIT). The Coffea arabica L. (coffee) crop in Amazonas, San Martín and Junín would retain its agricultural suitability in 2040 with a degree of optimal suitability greater than 83%; while Piura, with a SUIT of less than 17%, would no longer have optimal climatic conditions for the development of this crop. The suitability of Musa paradisiaca L. (banana) in Amazonas, Loreto, Cerro de Pasco, San Martin, Pucallpa and Madre de Dios, would present favourable conditions for its development, with Loreto having the greatest presence of areas with positive changes with respect to climatic suitability for the period 2041-2060, with a variable trend up to 60%. In Ucayali, Cuzco, Junín, Madre de Dios and Puno, the opposite is the case, regions with the greatest presence of areas that would suffer negative changes with respect to climate suitability for the period 2041-2060, with changes of up to -72%. Finally, climate suitability will move in areas no lower than 121 m and no higher than 1980 m above sea level (ms.n.m).